Acid and Solvent Effects on the Regioselectivity of Minisci-Type Addition to Quinolines Using Amino Acid Derived Redox Active Esters - Hadrys, Barbara W.; Phipps, Robert J. (Synlett, 2021)
Minisci-type reactions comprise an important class of reactions for the direct functionalization of basic heterocyclic compounds. On certain heterocycles, such as quinolines, Minisci-type reactions face a regioselectivity choice which often results in mixtures of regioisomers at the C2 and C4 positions, limiting utility. We present a study of the effect of solvent and Brønsted acid catalyst on regioselectivity in the addition of N-acetyl-substituted, α-amino alkyl radicals to quinolines. By tuning the solvent and acid combination we identify conditions that strongly favour C2 and strongly favour C4 and present a small scope of compatible substrates.
Keywords: Minisci reaction; regioselectivity; Brønsted acid; heterocycles; radicals